Psychopathological aspects of transsexualism - Zuanazzi, Gianfrancesco (Medicina e Morale, 2024)
We call transsexuals those individuals who - despite possessing genetic, physiological and morphological characteristics that are male, if they are a man, or female, if they are a woman - experience themselves as belonging to the opposite sex and desire the anatomical transformation of their bodies.